Food safety knowledge, needed and trusted information of pork consumers in different retail types in Northern Vietnam - Le, Trang Thi-Huyen; Langley, Shonara Jayde; Dunham, Jordan Gibson; Dang-Xuan, Sinh; Unger, Fred; Ngo, Hai Hoang Tuan; Nguyen-Thanh, Luong; Nguyen-Viet, Hung; Toribio, Jenny-Ann (Frontiers in Sustainable Food Systems, 2022)
Introduction Food safety is an important public health concern globally. Risk communication is one of crucial element to manage food safety. While current food safety studies have focused on contamination of hazards or risk factors, limited research exists on consumer concerns, knowledge and perception about the actual risk food poses to their health. This study aimed to assess and compare the knowledge and perceptions regarding food safety, and the information needed and trusted by pork consumers in Northern Vietnam. Methods A total of 225 consumers recruited from three different market types: modern urban, traditional urban and traditional rural, were interviewed using a questionnaire between November to December 2019. Results The majority of participants (81.8%) were female and consumers interviewed at modern urban retail were younger than those interviewed at traditional retail settings (p < 0.01). Sixty-five percent of participants across the three retail types agreed that microbes were the most common hazards which can make them sick, but the adverse health effect due to chemical hazards was ranked higher than that of biological hazards. Most participants often received food safety information that was about animal diseases (such as African swine fever most recently), chemical contamination and the unknown origin of food rather than about food poisoning and measures to prevent it. Food safety messages from television and professional experts were the most trusted sources and consumer preference was for information about the origin of food (traceability) and how to choose safe food. Participants were willing to receive food safety information daily to weekly. A lack of perception and awareness about animal welfare related to pig farming or slaughtering was reported by most respondents (84.3%). Discussion These findings provide insight on Vietnamese consumer knowledge gaps, information demand and communication channels for food safety, so that risk communicators and managers can implement better food safety awareness campaigns and communication to consumers.